2021
DOI: 10.1039/d1an01379c
|View full text |Cite
|
Sign up to set email alerts
|

Infrared microspectroscopy studies on the protective effect of curcumin coated gold nanoparticles against H2O2-induced oxidative stress in human neuroblastoma SK-N-SH cells

Abstract: The contribution of oxidative stress in several chronic and degenerative diseases suggests that antioxidant therapy can be a promising therapeutic strategy. However, in the case of many antioxidants, their biodistribution...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…[4][5][6] Molecular antioxidants can be found in plants and in the human body as well, but synthetic representatives are also known. 7,8 Immobilization in/on various nanoparticles is a common tool to enhance the sensitivity (against pH, light, pressure, temperature, ionic strength, etc.) of both enzymatic and non-enzymatic substances, which can facilitate biomedical and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Molecular antioxidants can be found in plants and in the human body as well, but synthetic representatives are also known. 7,8 Immobilization in/on various nanoparticles is a common tool to enhance the sensitivity (against pH, light, pressure, temperature, ionic strength, etc.) of both enzymatic and non-enzymatic substances, which can facilitate biomedical and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The transmittance spectrum was obtained with melanin samples exposed to Cr(VI) and using non-exposed samples as control. The spectra of Cr(VI)-exposed melanin were acquired by subtracting the reference spectra from non-exposed raw melanin (4000-600 cm −1 ) according to the method of Karimi et al (2021). The subtraction was done directly (automatically) using the OPUS 7.5 software (Bruker, Germany).…”
Section: Physicochemical Characterization Of Melaninmentioning
confidence: 99%
“…Binding a powerful scavenger such as curcumin has been shown to increase the efficacy of the scavenging and reduction of ROS throughout the body. One study found that this joint compound improved the efficiency of curcumin significantly due to the ability of Au to travel through the movement of water in the body (Karimi et al, 2021). This allows for Au to be potentially used as a radioprotective delivery agent, which has many different biomedical impacts with various compounds in the future.…”
Section: Noble Metal (Gold Silver and Platinum) Nps As Radioprotectantsmentioning
confidence: 99%